Composite vortex beams by coaxial superposition of Laguerre–Gaussian beams. (March 2016) - Huang, Sujuan; Miao, Zhuang; He, Chao; Pang, Fufei; Li, Yingchun; Wang, Tingyun
Abstract: We propose the generation of novel composite vortex beams by coaxial superposition of Laguerre–Gaussian (LG) beams with common waist position and waist parameter. Computer-generated holography by conjugate-symmetric extension is applied to produce the holograms of several composite vortex beams. Utilizing the holograms, fantastic light modes including optical ring lattice, double dark-ring and double bright-ring composite vortex beams etc. are numerically reconstructed. The generated composite vortex beams show diffraction broadening with some of them showing dynamic rotation around beam centers while propagating. Optical experiments based on a computer-controlled spatial light modulator (SLM) verify the numerical results. These novel composite vortex beams possess more complicated distribution and more controllable parameters for their potential application in comparison to conventional optical ring lattice.